Domestic Factors and Leaders in Foreign Policy Making: The Cases of Nasser and Morsi - Duman, Ahmed Hayri (My University, 2021)
It has been a general assumption that leaders have played a vital role in the makingof Egypt's foreign policy. This article tries to detail this assumption and illustrates thatindividual formulation and implementation of foreign policies following the FreeOfficers' coup d'etat of 1952 and the Egyptian revolution of 2011 cannot be sufficientlyclarified in the absence of domestic level explanations. What is found in this study isthat various domestic factors paved the way for Nasser to increase his effectiveness onEgypt's foreign policy, whereas they created a compelling environment for Morsi inwhich he had a lesser influence on its foreign policy during his short tenure.

Liderlerin Mısır'ın dış politikasının oluşturulmasında çok önemli oyuncular olduğu genel bir varsayımdır. Bu makale bu varsayımı detaylandırmaya çalışmakta ve 1952 Hür Subaylar Darbesi ve 2011 Mısır devriminden sonra dış politikaların bireysel olarak formüle edilmesi ve uygulanmasının yerel düzeydeki açıklamaların yokluğunda açıklığı kavuşturulamayacağını göstermektedir. Bu çalışmada, çeşitli yerel faktörlerin Nasır'ın Mısır'ın dış politikası üzerindeki etkinliğini artırmasına zemin hazırladığı, Mursi için ise zorlayıcı bir ortam oluşturarak kısa görev süresince dış politika üzerinde daha az etkili olmasına sebep olduğu bulundu.
Dış Politika Yapımında Liderler ve Yerel Etkenler: Nasır ve Mursi Örnekleri
Keywords: Egypt; Nasser; Morsi; Foreign Policy; Domestic Level of Analysis; Mısır; Nasır; Mursi; Dış Politika; Yerel Analiz Seviyesi